2020
DOI: 10.1144/jgs2020-163
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes (δ 13 C, δ 18 O) and element ratios (Mg/Ca, Sr/Ca) of Jurassic belemnites, bivalves and brachiopods from the Neuquén Basin (Argentina): challenges and opportunities for palaeoenvironmental reconstructions

Abstract: Fossils from the Jurassic succession of the Neuquén Basin (Argentina) were analysed for their stable isotope (δ13C, δ18O) and elemental (Mg/Ca, Sr/Ca) composition. Mg/Ca ratios point to comparatively stable temperature conditions from the Bajocian to Early Oxfordian and during the Tithonian, but do not allow a reliable reconstruction of absolute water temperatures. Sr/Ca ratios follow the general global pattern indicating water exchange between the basin and the open ocean. The δ18O values can be translated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…It was separated from the Palaeo-Pacific by a volcanic arc forming an island chain (e.g., Howell et al, 2005), but alternatively a continuous peninsula has been suggested (Vicente, 2005). Water exchange between Palaeo-Pacific and Neuquén Basin was thus more or less restricted but Sr/Ca ratios of marine carbonates nonetheless imply a rather permanent connection between both water bodies since the Sr/Ca values are in the same range (e.g., Alberti et al, 2020).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…It was separated from the Palaeo-Pacific by a volcanic arc forming an island chain (e.g., Howell et al, 2005), but alternatively a continuous peninsula has been suggested (Vicente, 2005). Water exchange between Palaeo-Pacific and Neuquén Basin was thus more or less restricted but Sr/Ca ratios of marine carbonates nonetheless imply a rather permanent connection between both water bodies since the Sr/Ca values are in the same range (e.g., Alberti et al, 2020).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…1), Upper Jurassic-Lower Cretaceous belemnite records are sparser and poorly known. Oxfordian Belemnopsis with European affinities have been mentioned from La Manga Formation in southern Neuquén (Doyle et al, 1996;Riccardi et al, 2011) and from the Callovian-Oxfordian of Vega de la Veranada, in northern Neuquén (Alberti et al, 2020). Younger not-illustrated records from Mendoza Province include an indeterminate rostrum fragment from the Tithonian of Arroyo Serrucho (Krantz, 1928) and some thin incomplete rostra from the upper Tithonian of the Vaca Muerta Formation in Bardas Blancas (Gerth, 1925; here referred as Cañada de Leiva).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Moreover, times of carbonate deposition might be associated with cooler climates. For instance, during deposition of the Picún Leufú Formation carbonates in the southern part of the basin (late Tithonian-early Berriasian, Leanza et al, 2020), Alberti et al (2020) recorded a cold snap (18 • C) using bivalve oxygen isotope data. However, Gómez-Dacal et al ( 2018) calculated relatively warm temperatures (~25 • C) in the northern Neuquén Basin at the same time.…”
Section: Sedimentologic Implications For the Vaca Muerta Formationmentioning
confidence: 99%